Safety Status of Schools in Shiraz and its Related Factors - Soheila Shaghaghian; Belgheys Malekzadeh; Mehrab Sayadi (Shiraz University of Medical Sciences, 2017)
Objectives: Due to the high impact of school safety on students' health, this study was conducted to determine safety status of the schools of Shiraz and its related factors. Methods: In this cross-sectional study, 310 schools of Shiraz during year 2013 were selected by randomized multi-stage sampling. Our data-gathering tool was a valid and reliable researcher-made questionnaire which was designed based on the school health guideline standardized by Institute of standards and industrial research of Iran. Using this questionnaire, 12 items of school safety were evaluated. Safety status of the schools, overall and in each item, was calculated from the total score of 100. The relationship between school characteristics and its safety status was also evaluated using the SPSS software and the following statistical tests: Spearman's correlation, independent sample t-test, one-way Analysis of Variance (ANOVA) with Tukey's post-hoc test. Statistical significance was set at P < 0.05. Results: The mean of the overall school safety was 63.72 ± 8.97. Among safety items of the schools, the mean of the fire control item had the least score (34.03 ± 14.16). Overall school safety was significantly better in larger schools, in schools with more land area (P = 0.009), more yard surface area (P = 0.044), higher number of classes (P = 0.003), and higher number of staffs (P = 0.006). However, there were no significant differences between overall safety scores of elementary, middle, and high schools (P = 0.098), as well as between governmental and private schools (P = 0.954). Conclusions: Safety status of Shiraz schools, especially in fire control item, was not desirable. Therefore, interventions for improving the status are necessary. Safer heating system should be used in schools and all schools should have appropriate fire extinguishers. These interventions are necessary for all school grades, including elementary, middle and high schools, and for both governmental and private schools.